FOCT: A collaborative system for CASE tools users / Zhu Lizhong - Zhu , Lizhong (2007)
CASE tools have already been used for many years in IT organizations. Although CASE tools bring many benefits to organizations there are many issues during the implementation of CASE tools. This research aims to investigate the utilization of CASE tools in both educational and industrial environments in Malaysia, followed by success factors and obstacles affecting the use of CASE tools and create a web-based system called the Forum of CASE Tools (FOCT). To meet these three objectives, the researcher conducted interviews with IT professionals from the industry; and conducted surveys through questionnaires among IT students and lecturers from colleges and universities. After analyzing the data collected from the target groups, the researcher is clearer on the status of CASE tools utilization in both the educational and industrial sectors. Some success factors and obstacles were identified from the target groups. Based on the data collected, the researcher developed a web-based system called Forum of CASE Tools system (FOCT). This allows the CASE tool users to share their knowledge and experience in using CASE tools and promote the utilization of CASE tools in Malaysia. By doing this research, a better understanding of using CASE tools in Malaysia has been achieved. More importantly, this research would be able to help educators train knowledge workers for this information age.